HUBUNGAN KONSUMSI ASAM LEMAK OMEGA-3, AKTIVITAS FISIK DAN PERSEN LEMAK TUBUH DENGAN TINGKAT DISMENORE PADA REMAJA - Famimah, Famimah; Margawati, Ani; Fitranti, Deny Yudi (Journal of Nutrition College, 2017)
Background: Dysmenorrhea or menstrual pain was a gynecological complaint due to an imbalance of progesterone in the blood resulting in pain. A woman with dysmenorrhea should consume food rich in omega-3 fatty acids such as fish oil, fish (salmon, tuna, mackerel, herring), soybeans and fruits. Low fish consumption was related with severity of dysmenorrhea. In addition, physical activity and percent body fat were also associated with severity of dysmenorrhea.Objective : To determine the correlation between consumption of omega-3 fatty acids, physical activity and percent body fat to the classification of dysmenorrhea in adolescents.Methods : Cross sectional study of 90 adolescentsselected by purposive sampling. This research was conducted in SMA N 15 and SMA N 9 Semarang. Menstrual history was measured by direct interviews and level of dysmenorrhea was measured using Numerical Rating Scale Questionnaire. Omega-3 fatty acids were measured using Food Frequency Questionnaire (FFQ) and analyzed using a nutritional software program. Physical activity was measured using A short questionnaire for the measurement of habitual physical activity in epidemiological studies. Percent body fat was measured using Bioelectrical Impedance Analysis (BIA). Data were analyzed by Independent T test/Mann Whitney. Result : There were significant correlation in omega-3 fatty acid (p= 0,015), and percent body fat (p= 0,026). While in physical activity there was no significant correlation (p= 0,394).Conclusion : Consumption of omega-3 fatty acids and percent body fat were associated with the classification of dysmenorrhea.